2013
DOI: 10.1128/genomea.00668-13
|View full text |Cite|
|
Sign up to set email alerts
|

Complete Genome Sequences of Five Paenibacillus larvae Bacteriophages

Abstract: Paenibacillus larvae is a pathogen of honeybees that causes American foulbrood (AFB). We isolated bacteriophages from soil containing bee debris collected near beehives in Utah. We announce five high-quality complete genome sequences, which represent the first completed genome sequences submitted to GenBank for any P. larvae bacteriophage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Prior to this study, 15 phages of P. larvae were described, and phage HB10c2 exhibits structural similarities to them (31). According to recent developments and further classification of phages at the genomic level in the International Committee on Taxonomy of Viruses, phage HB10c2 could be grouped into the proposed genus "Divavirus.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this study, 15 phages of P. larvae were described, and phage HB10c2 exhibits structural similarities to them (31). According to recent developments and further classification of phages at the genomic level in the International Committee on Taxonomy of Viruses, phage HB10c2 could be grouped into the proposed genus "Divavirus.…”
Section: Discussionmentioning
confidence: 99%
“…pulvifaciens isolates (DSM 8442 and DSM 8443) being labeled as "unverified." These results also led to the reclassification of our field isolates as B. laterosporus (Br1 to Br14) (17). However, due to the genotypic, phenotypic, and ecological similarities of these two genera, as well as the reported frequencies of horizontal gene transfer within bacteria that share an ecological niche, reliance on a single gene to assign taxonomy can be perilous.…”
Section: Resultsmentioning
confidence: 84%
“…Researchers working to detect P. larvae in beehives often isolate B. laterosporus and other closely related bacteria due to insufficient discriminatory techniques for these similar species (1-5). Our field isolates Br1 to Br10 and Br14 were initially classified as P. larvae based on their isolation on selective media, the absence of catalase activity, PCR-amplified 16S rRNA sequence similarity to P. larvae, and other previously described tests (17,20). BLASTN (24)(25)(26) results indicated that the partial 16S rRNA gene sequences of the 11 strains, previously reported as PL1 to PL10 and PL14 but here reclassified as Br1 to Br10 and Br14 (18), shared an average of 97% identity (range, 93 to 99%) with the 16S rRNA gene from two P. larvae subsp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations